The effect of the generative learning strategy on the accuracy of performing some basic skills of some collective games (Journal of the College of Basic Education, 2022)
The study aimed to identify the impact of the generative learning strategy on the accuracy of the performance of some basic skills for some collective games, which are (basketball, volleyball, and handball). They were chosen according to their learning through the test, and were divided into (6) groups. Experimental and control for each of the three games, to be three experimental groups, each of which corresponds to a control group, and accuracy skills were determined from each game and specific tests for it, and three educational curricula were prepared for each game, its own curricula dealing with accuracy only, as each educational curricula contained (4 ) Educational units with a time of (45) minutes given one unit per week for a period of four weeks, and it was the most important